2015
DOI: 10.1371/journal.pone.0129303
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of H9c2 Myoblast Differentiation towards a Cardiac-Like Phenotype

Abstract: H9c2 myoblasts are a cell model used as an alternative for cardiomyocytes. H9c2 cells have the ability to differentiate towards a cardiac phenotype when the media serum is reduced in the presence of all-trans-retinoic acid (RA), creating multinucleated cells with low proliferative capacity. In the present study, we performed for the first time a transcriptional analysis of the H9c2 cell line in two differentiation states, i.e. embryonic cells and differentiated cardiac-like cells. The results show that RA-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
152
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(162 citation statements)
references
References 38 publications
8
152
2
Order By: Relevance
“…1D-F). We finally observed that the duplication time of H9C2 cells was two days, in line with previous results 14 (Fig. 1G); meanwhile, after the differentiation protocol, the rate of proliferation decreased (Fig.…”
Section: H9c2 CM Population Demonstrates Increased Expression Of Cardsupporting
confidence: 91%
See 1 more Smart Citation
“…1D-F). We finally observed that the duplication time of H9C2 cells was two days, in line with previous results 14 (Fig. 1G); meanwhile, after the differentiation protocol, the rate of proliferation decreased (Fig.…”
Section: H9c2 CM Population Demonstrates Increased Expression Of Cardsupporting
confidence: 91%
“…They confirmed the presence of a cardiomyocyte-like phenotype by identifying mRNAs related to cardiac muscle and mitochondrial metabolism as being upregulated on a transcriptional level relative to those in H9C2. 14 However, their study was restricted to investigating changes in the transcriptome, which does not always correlate with the functional proteome; 15 therefore, their findings require support from a quantitative and systematic proteomics analysis. This requirement is further reinforced by the pervasive role of micro RNAs in the post-transcriptional regulation of gene expression in cardiomyocytes during differentiation and disease.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the reduction of both proliferation rate and expression of the specific markers agree with previous reports investigating cardiomyocyte‐like differentiation and were mainly accounted for a shift in cardiomyocyte maturational status that has not been yet occurred as H9c2 required additional time to adapt to the scaffold.…”
Section: Discussionsupporting
confidence: 90%
“…The H9c2 cell line is currently used as a gold standard in vitro model as, due to its biochemical, morphological and electrical/hormonal signaling properties, it is able to mimic the behavior of skeletal and cardiac muscle . A preliminary goal of the study was to evaluate any phenotypical changes of H9c2 cell line, due to two different culture conditions: FBS reduction (from 10% to 1%) and all‐trans retinoic acid culture enrichment . In fact, one important feature of this cell line is its ability to differentiate from mononucleated myoblasts to myotubes when cultured in a low serum concentration media, getting an elongated shape and positioning in a parallel fashion .…”
Section: Discussionmentioning
confidence: 99%
“…These cells have the ability to differentiate into cardiomyocyte-like cells when they are exposed to all-trans retinoic acid in reduced-serum media. After differentiation, H9c2 cells express a more cardiac-like phenotype such as having a greater mitochondrial mass 31 , as well as having an increased expression of proteins involved in Ca 2+ handling and mitochondrial metabolism 41 . Such characteristics are of importance in these studies since the particles being tested were designed to target the mitochondria of cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%